Georgian and Soviet : entitled nationhood and the specter of Stalin in the Caucasus - Kaiser, Claire P., 1984- (Cornell University Press, 2022)
"Drawing on extensive research in Georgian archives and Georgian-language sources, this book argues that the postwar and post-Stalin era was decisive in the creation of a 'Georgian' Georgia due to not only the role played by the Stalin cult in the construction of Georgian nationhood but also the changes that de-Stalinization wrought among Georgia's populace and in the relationship between Moscow and Tbilisi"--